Sensory optimization of a mayonnaise-type spread made with rice bran oil and soy protein - Karen Garcia (2018)
The optimum formulation for mayonnaise-type spreads containing rice bran oil (RBO) and soy protein concentrate (SPC) was determined based on sensory acceptability. RBO and SPC were used due to their health benefit claims such as lowering risk of heart disease. The effects of the proportions of high-impact ingredients (RBO, SPC, andwater) on sensory acceptability of the spreadswere determined. The 10 spread formulations, prepared following a 3-component constrained simplex lattice mixture design, were subjected to a consumer acceptance test to identify sensory attributes driving consumer acceptance and purchase intent. Predictive regression models were used to plot mixture response surfaces of the critical sensory attributes (taste, mouthfeel, and overall liking) that influenced purchase intent. Areas within the contour plots of these critical sensory attributes, having acceptability scores > 68 (-moderately like- on the 100-mm bidirectional labeled affectivemagnitude scale) were chosen and superimposed to obtain a predicted optimum formulation range (37% to 43% RBO, 4% to 7% SPC, and 52% to 57% water). The formulation containing 37% RBO, 6% SPC, and 57% water, which was located within the optimum region, was selected as a base for further developing flavored (sour cream & onion, cheddar & sour cream, orMonterrey Jack dried cheese) products. All flavored spreads were significantlymore acceptable than the plain formulation. Purchase intent of all flavored products also significantly increased once consumers had been given the information about potential health benefits associated with RBO and SPC in the spreads. © 2009.